Factors Related to Selection of Birth Attendants for Mothers in Labor in Malawele Aimas District Sorong Regency Year 2015 - Sunaeni, Sunaeni (International Conference on Sustainable Health Promotion, 2018)
The low coverage of childbirth assisted by skilled birth attendants can be influenced by the attitude and behavior of pregnant mothers in choosing the birth attendants. From the prior study, it can be found that 6 out of 10 mothers (60%) had delivery in unskilled birth attendants, and 3 of them were not supported by their family (30%). There were four mothers were had delivery assisted by skilled birth attendants and all of them were encouraged by their family. The purpose of this study was to determine the factors related to choosing the birth attendants for the mothers in Urban Village Malawele Aimas District. The design of the research is correlational analytic with the cross-sectional approach. The population is all mothers in labor in Urban Village Malawele Aimas District with the total of 60 mothers, sampling used was saturated sample. Data were analyzed using Chi-Square with significance level 0,05. The result of the study stated that there was the relationship among knowledge, income, family support in choosing the birth attendants. It is recommended that healthcare facilities improve the coverage of childbirth assisted by skilled birth attendants. As for the community to be able to utilize health facilities as the place for delivery.